Analisis Strategi Pemasaran Tetu Fresh Di Balai Kota Selatan Kota Palu - Syabilla, Tiara Adita; Putri, Widya Mega; Fazira, Intan; Rosada, Sabania Amrina; Rachmad; Aqib (JPS: Journal of Publicness Studies, 2025)
ABSTRACT This study aims to analyze the marketing strategy implemented by the Micro, Small, and Medium Enterprise (MSME) Tetu Fresh in South Balai Kota, Palu, Central Sulawesi. This traditional sweet food is very popular and easy to find in Palu City, especially during the month of Ramadan. The type of method used in this study is a qualitative research method by conducting direct and in-depth interviews and documentation with two informants: the owner and employee of Tetu Fresh, which operates on Jalan Balai Kota Selatan, Palu. The results show that Tetu's marketing strategy is carried out through word of mouth promotion, attendance at culinary events, promotions via WhatsApp, and short content on Instagram and TikTok, which have proven very helpful in developing the business and making it more known to many people. However, there are several challenges for this business owner, such as the need for raw materials that must be truly high quality and maintaining kitchen hygiene, because when cooking, customers directly see the process.